The Role of Social Activism Representative Board of Indonesian National Youth Committee (BP-KNPI) in Malaysia During Movement Control Order 2020-2021 - Abadi, Mansurni; Wulandari , Wulandari (Antroposen: Journal of Social Studies and Humaniora, 2022)
Through activism, community organization, and engagement in social movements, youth worldwide are becoming active actors, demonstrating their ability to influence society in times of crisis. In the context of Indonesian youth, especially those who are part of the diaspora community, attachment to fellow children of the nation is evidenced by social activism, as was the case in Malaysia during the movement control order between 2021 and 2022 through the representative body of the Indonesian Youth National Committee (BP-KNPI). Since its establishment on October 9, 2011, the Indonesian Youth National Committee (BP-KNPI), the representative body for Indonesian youth in Malaysia, has been proactive in playing its role as a second-track diplomatic force, advocating for youth and employment issues, and engaging in social activism to help Indonesian communities in Malaysia. During the pandemic period between March 2020 and December 2021, with the movement control order policy, the representative body of the Indonesian Youth National Committee (BP-KNPI) plays a role in social activism in three domains: (1) the field of employment by supporting the labour recalibration program, which repatriates illegal Indonesian workers in Malaysia (2). in the humanitarian realm by organising assistance from both internal and external parties, such as the Indonesian embassy in Kuala Lumpur; and (3). conducting second-track diplomacy to strengthen relations with the Malaysian Young Council and elements of the Malaysian government. In cyberspace, BP-KNPI Malaysia is also very active in raising solidarity and providing information related to recalibration programmes and social assistance through its members' potential as content creators and relationships with well-known media. Our research concludes that BP-KNPI Malaysia, as a youth civil society, has always been proactive in problem-solving during the pandemic through social activism in humanity, migrant workers from Indonesia, and legal literacy in cyberspace. BP-KNPI Malaysia also tactically implements the spirit of energy and harmony promoted by DPP-KNPI.